Application of EIA/SEA system in land use planning: Experience from Serbia - Stojanović Božidar (Spatium, 2005)
This paper discusses the experience and current status of EIA/SEA procedures and assessment methodologies in Serbia, aiming to propose strategies that can lead to effective integration of the SEA in spatial planning. Institutional and practical problems with regard to the regulations of EIA/SEA were considered. Experience from the past decade shows that implementation of EIA system in Serbia has not been effective as expected. New legislation on EIA and SEA is harmonized with corresponding EU Directives. First steps in the application of the SEA show that the main issues are screening, scooping and decision making. According to the research results, it is suggested that extra evaluation processes should be incorporated into current assessment procedures to improve their scientific validity and integrity.